Effect of cutting parameters on surface roughness tool temperature and vibration in turning of AISI 316 Ti stainless steel - Ay, Mustafa (Carl Hanser Verlag, 2019)
The effects of turning process parameters on surface roughness, tool vibration and temperature were investigated for an AISI316Ti steel. The parameters were optimized by the Taguchi method. Experiments were performed using the L-9 orthogonal array (Ti, Al) N + TiN coated carbide cutting tools in dry conditions. ANOVA and S/N ratio were used to optimize the cutting parameters. The most dominant factor affecting tool vibration and tool temperature was determined as cutting speed and the most dominant factor affecting surface roughness was feed rate. The optimum parameter combination developed by the Taguchi method was confirmed with the help of confirmation tests. As a result, with the help of optimization, the surface roughness was reduced from 1.421 mu m to 1.204 mu m and the tool vibration was reduced from 0.01454 mm to 0.00758 mm.
Keywords: AISI 316Ti; Taguchi process; ANOVA; cutting; surface roughness; tool vibration; temperature